Migratory movements and wintering areas of Leach's Storm‐Petrels tracked using geolocators. Issue 3 (26th August 2014) - Pollet, Ingrid L.; Hedd, April; Taylor, Philip D.; Montevecchi, William A.; Shutler, Dave
ABSTRACT Accumulating evidence suggests that Atlantic populations of Leach's Storm‐Petrels (Oceanodroma leucorhoa) are experiencing significant declines. To better understand possible causes of these declines, we used geolocators to document movements of these small (∼50‐g) pelagic seabirds during migration and the non‐breeding period. During 2012 and 2013, movement tracks were obtained from two birds that traveled in a clock‐wise direction from two breeding colonies in eastern Canada (Bon Portage Island, Nova Scotia, and Gull Island, Newfoundland) to winter in tropical waters. The bird from Bon Portage Island started its migration towards Cape Verde in October, arrived at its wintering area off the coast of eastern Brazil in January, and started migration back to Nova Scotia in April. The bird from Gull Island staged off Newfoundland in November and then again off Cape Verde in January before its geolocator stopped working. Movements of Leach's Storm‐Petrels in our study and those of several other procellariiforms during the non‐breeding period are likely facilitated by the prevailing easterly trade winds and the Antilles and Gulf Stream currents. Although staging and wintering areas used by Leach's Storm‐Petrels in our study were characterized by low productivity, the West Africa and northeastern Brazilian waters are actively used by fisheries and discards can attract Leach's Storm‐Petrels. Our results provide an initial step towards understanding movements of Leach's Storm‐Petrels during the non‐breeding period, but further tracking is required to confirm generality of their migratory routes, staging areas, and wintering ranges.